Preventive Behaviors, Barriers, and Drivers of the COVID-19 Pandemic in Malaysia: A Cross-sectional Survey - Ab Malik, Normaliza; Mohd, Rusyda Helma; Abdul Kadir, Nor Ba'yah (Makara Journal of Health Research, 2021)
Background: Coronavirus disease 2019 (COVID-19) is a public health concern worldwide. This study aimed to assess the preventive behaviors, barriers, and drivers, including the knowledge and self-efficacy of COVID-19 in Malaysia. Methods: A cross-sectional study was conducted during the COVID-19 outbreak by using a self-administered questionnaire. The instrument used was adopted from the World Health Organization resources. Descriptive statistics were used to describe the categorical data. Chi-square and independent t-test were performed to evaluate the associations between the variables and preventive behaviors. Results: A total of 465 (97.3%) respondents were recorded. The mean age was 34.3 ± 11.8 years old. A high percentage of the respondents (99.4%) were aware of the COVID-19 outbreak, and their knowledge mean score was 18.74 (Standard Deviation [SD]: 2.51). The mean scores of self-efficacy, barriers, and drivers were 11.07 (SD: 1.72), 5.20 (SD: 2.81), and 39.71 (SD: 5.17), respectively. Barriers (Odds Ratio [OR]: 1.10; 95% Confidence Interval [CI]: 1.01, 1.21; p < 0.05) and drivers (OR: 1.12; 95% CI: 1.07, 1.17; p < 0.001) were found to be predictors for social distancing practices. Conclusions: Knowledge and self-efficacy were found to be at good levels, whereas self-efficacy, barriers, and drivers were revealed to be the predictive factors in determining the preventive behaviors. Adherence to preventive measures was largely affected by the behavioral drivers.